Contextual inequalities in specialized dental public health care in Brazil - Ana Luiza Cardoso PIRES; Francine dos Santos COSTA; Otávio Pereira D'ÁVILA; Rodrigo Varella de CARVALHO; Marcus Cristian Muniz CONDE; Marcos Britto CORREA; Flávio Fernando DEMARCO; Luiz Alexandre CHISINI (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract The present study aimed to investigate the contextual inequalities of specialized public dental care (SPDC) in Brazil. The outcome was the trajectory of dental specialized production in municipalities with SPDC (from 2015 to 2017) obtained by group-based trajectory modeling. A Poisson regression model was used to analyze the factors associated with the high trajectory of SPDC production. The inequality indicators for SPDC production were the slope index and the concentration index according to contextual factors. The study included 954 SPDC units distributed across 893 municipalities. Among the municipalities evaluated, 62.9% had a low trajectory of SPDC. Large-sized municipalities had the highest production (IRR = 2.84, 95%CI: 1.94-4.14) and the southern region had the lowest production (IRR = 0.73, 95%CI: 0.58-0.92). Municipalities presenting a very high human development index (HDI) showed the greatest SPDC production (IRR = 3.34, 95%CI: 1.09-10.24), as well as municipalities with the highest tertile of schooling rate (IRR = 1.23, 95%CI: 1.00-1.50). The absolute inequality was 52.1 percentage points for the average monthly wage (p < 0.001), 61.0 percentage points for the HDI (p < 0.001), -22.1 for infant mortality rate (p <0.001), and 14.8 for the schooling rate (p = 0.012). Thus, there are contextual inequalities in the Brazilian SPDC. Higher scores for social indicators were associated with better SPDC performance.